Design and Performance Verification of Dynamic Load Aware Geographic Routing Protocol in IEEE 802.15.4a Networks. (21st May 2014) - Kim, Young-Duk; Kwon, Soon; Son, Joon-Woo; Kim, Dongkyun
Abstract : Although the IEEE 802.15.4a network provides accuracy localization for sensor nodes, it still suffers from congestion and bottleneck problems since the data traffic tends to concentrate on a certain intermediate node due to the shortest path first criteria when it utilizes a greedy routing method. Furthermore, the limited network bandwidth and node mobility features exacerbate this problem in wireless sensor networks with tiny sensor platforms. In this paper, we propose a new dynamic load aware geographical routing protocol, named DLAG, which periodically monitors the channel condition of each node and forwards a packet to the neighboring node with the least traffic load by defining new buffer threshold values for controlling the congestion. In addition, the proposed protocol also introduces traffic adaptive backoff and frame retransmission tuning techniques to provide prioritized channel access for congested nodes. In order to verify the performance of the proposed protocol, we conduct simulation verification experiments and the results show that the proposed protocol provides better performance than the legacy geographical routing schemes in terms of packet delivery ratio, end-to-end delay, network lifetime, and so forth.